1986
DOI: 10.1128/mcb.6.12.4594
|View full text |Cite
|
Sign up to set email alerts
|

Identification of temperature-sensitive DNA- mutants of Chinese hamster cells affected in cellular and viral DNA synthesis.

Abstract: We described a strategy which facilitates the identification of cell mutants which are restricted in DNA synthesis in a temperature-dependent manner. A collection of over 200 cell mutants temperature-sensitive for growth was isolated in established Chinese hamster cell lines (CHO and V79) by a variety of selective and nonselective techniques. Approximately 10% of these mutants were identified as ts DNA-based on differential inhibition of macromolecular synthesis at the restrictive temperature (39°C) as assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…A 6-thioguanine (TG)-resistant clone deficient in the enzyme hypoxanthine-guanine phosphoribosyltransferase (hprt-) was isolated from ts2O in Plasmids. p53A6.6 containing the whole polyomavirus genome cloned at the BamHI site in pAT153 was propagated and harvested from DH-1 (dam') bacteria as previously described (9,29).…”
Section: Matermils and Methodsmentioning
confidence: 99%
“…A 6-thioguanine (TG)-resistant clone deficient in the enzyme hypoxanthine-guanine phosphoribosyltransferase (hprt-) was isolated from ts2O in Plasmids. p53A6.6 containing the whole polyomavirus genome cloned at the BamHI site in pAT153 was propagated and harvested from DH-1 (dam') bacteria as previously described (9,29).…”
Section: Matermils and Methodsmentioning
confidence: 99%
“…Moreover, this effect was observed even when the cells had been previously infected at 33°C, indicating that ongoing viral DNA synthesis was also affected. Since viral DNA synthesis would not be expected to be cell cycle dependent nine-free medium for 2 h, and incorporation into macromolecules was deterniined as previously described (9).…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, few conditional DNA-defective mutants are available in mammalian cells, a fact that limits the use of genetic approaches to an understanding of their DNA metabolism (28). Dermody et al (9) have previously reported the isolation, utilizing a variety of selective and nonselective conditions, of a large collection of Chinese hamster cell mutants that are temperature sensitive for growth. Biochemical screening has identified a subset of nine mutants that were designated temperature-sensitive DNA (tsDNA) mutants, as they exhibited rapid inhibition of DNA synthesis but not protein synthesis upon shift of growing cultures from the permissive temperature (33°C) to the nonpermissive or restrictive temperature (39.5°C).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chinese hamster fibroblast CHO-K1 was cultured in Dulbecco's modified Eagle's medium/F-12 medium (Invitrogen) and 10% fetal bovine serum as described previously (35). Mouse NIH 3T3 fibroblasts were cultured in Dulbecco's modified Eagle's medium (Invitrogen) containing 1 mM sodium pyruvate (Sigma) and 10% bovine calf serum (Sigma) as described previously (36).…”
Section: Methodsmentioning
confidence: 99%